(untitled) (Revista da Faculdade de Odontologia - UPF, 2016)
Objective: The Glandular Odontogenic Cyst (GOC) is a rare benign odontogenic lesion, of considerable aggression, and often incorrectly diagnosed. We present a patient with a Glandular Odontogenic Cyst in the posterior mandible, its evolution, treatment, and follow-up. Case report: A female patient, 45 years old, was referred to the Oral and Maxillofacial Surgery and Traumatology Division at Cristo Redentor Hospital, Porto Alegre, Brazil, for the assessment of a painful edema on the right hemiface. A unilocular area with well-defined borders in the retromolar region, posterior to the third molar on the right side of the mandible. The histopathological examination suggested GOC. Final considerations: The Glandular Odontogenic Cyst needs a complete clinical assessment associated with image analyses, and especially, with histopathology for the correct diagnosis of the lesion, since the diagnosis may be mistaken in clinical and radiographic examination. There are several treatment options; however, enucleation associated with cryotherapy, in this case, was an effective method for the treatment of Glandular Odontogenic Cyst.